2017
DOI: 10.3389/fpsyg.2017.01926
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Defense Patterns and DSM-5 Maladaptive Personality Domains

Abstract: Aim: Research has extensively examined the relationship between defense mechanisms (DM) and personality traits. However, no study to date has explored if specific defenses (alone or in combination) are able to predict dysfunctional variants of personality domains, as conceived in the alternative DSM-5 model for personality disorders. This study aimed to investigate the relationship between DMs and DSM-5 maladaptive personality domains among adults.Materials and Methods: Three hundred and twenty-eight adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 76 publications
(95 reference statements)
8
41
0
6
Order By: Relevance
“…The present study explored the relationships among psychological trauma, dissociation, and maladaptive personality domains. Consistent with previous studies on other nonclinical samples from the same country, our sample reported only low to moderate levels of psychological trauma ( 36 ), maladaptive personality traits ( 43 , 44 ), and dissociative symptoms ( 3 ). Also consistent with the literature, males reported higher antagonistic features than females, and females reported higher negative affectivity than males ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study explored the relationships among psychological trauma, dissociation, and maladaptive personality domains. Consistent with previous studies on other nonclinical samples from the same country, our sample reported only low to moderate levels of psychological trauma ( 36 ), maladaptive personality traits ( 43 , 44 ), and dissociative symptoms ( 3 ). Also consistent with the literature, males reported higher antagonistic features than females, and females reported higher negative affectivity than males ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies on other nonclinical samples from the same country, our sample reported only low to moderate levels of psychological trauma ( 36 ), maladaptive personality traits ( 43 , 44 ), and dissociative symptoms ( 3 ). Also consistent with the literature, males reported higher antagonistic features than females, and females reported higher negative affectivity than males ( 44 ). The main aim of our study was to test a conceptual model in which the predictive association between trauma and maladaptive personality functioning would be mediated by dissociation.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, maladaptive traits have been found to be associated with a range of other variables, including age [75]; gender [75,217]; general symptom distress [66,77,84,172,[218][219][220]; psychotic disorder [221,222]; dissociative experiences [223]; bipolar disorder [224]; attention-deficit/hyperactivity disorder [225]; problematic alcohol use [66, 226‱]; substance use [140,227,228]; self-harm [229]; pathological gambling [230]; internet-gaming disorder [231]; problematic internet use [223]; posttraumatic stress disorder [232, 233‱]; physical illness [233‱]; disability [57, [234][235][236]; quality of life [149,236]; self-esteem [150]; alexithymia [150]; empathy, self-reflection, and insight [150]; maladaptive schemas [237]; interpersonal problems [150,238,239]; pathological beliefs [240]; defensive styles [241]; emotion dysregulation [150,242]; anxiety mindset [205]; impulsivity [227]; aggression…”
Section: Convergent Validitymentioning
confidence: 99%
“…The use of defense mechanisms during a global health crisis should be monitored because psychological health is closely related to the ability to appropriately use a variety of defenses in challenging contexts, and a predominant use of immature defenses is a risk factor for the development of different forms of adult psychopathology (Bond & Perry 2004, Zanarini et al 2009). Children and young adults should also be assessed from a psychodynamic perceptive given that an increased use of immature defenses and a reduced use of mature defenses have a negative impact on the development of personality (Granieri et al 2017). Indeed, seminal concepts such as the "rigidity" of personality or the "character armor" (Reich 1933(Reich /1979) clearly express the idea that mental health is strictly related to emotional flexibility.…”
Section: Resilience Posttraumatic Growth and Anti-fragility In Time mentioning
confidence: 99%